Is the German apprenticeship system a panacea for the U.S. labor market? - Harthoff, Dietmar [Verfasser]; Kane, Thomas J. [Verfasser] (My University, 1997)
"This paper explores the structure of incentives undergirding the German system of apprenticeship training. The author first describe characteristics of the German labor market which may lead firms to accept part of the cost of general training, even in the face of worker turnover. They then compare labor market outcomes for apprentices in Germany and high school graduates in the United States. Apprentices in Germany occupy a similar position within the German wage structure as held by high school graduates in the United States labor market. Finally, the authors provide evidence that - in both countries - the problem of forming labor market bonds in particularly acute for minority youth." (author's abstract, IAB- Doku) ((en)) In dem Beitrag wird untersucht, weshalb deutsche Unternehmen in die Berufsausbildung investieren, welchen Bildungsvertrag betrieblich Ausgebildete gegenüber High-School-Absolventen der USA erreichen und ob das deutsche Ausbildungssystem auf das amerikanische übertragbar ist. (IAB)
Keywords: S System beruflicher Bildung; S 1.3 Berufliche Erstausbildung; I 2.3.2 Nordamerika; Berufsbildungssystem; Internationaler Vergleich; Betriebliche Berufsausbildung; Ausbildungsinvestition; Einflussfaktor; Bildungsertrag; Quantitative Angaben; USA; 1979-1992